The Interface Between Work and Health in the Craft of Tour Guides - Alves, Kerley dos Santos; Araújo, José Newton Garcia (Journal of Tourism Management Research, 2016)
This article aims to analyze the relation between work and health in the professional practice of tour guides working in the tourist city of Ouro Preto, Minas Gerais state, Brazil. It is based on literature research covering the professionalization process of this professional category and the relation between work, mental health and illness. Data collection was conducted through free observation of the work environment as well as by means of semi-structured interviews with tour guides. The study concluded that the constant feeling of insecurity to which these professionals are exposed may cause emotional and psychic distress that turns into psychopathology, which in turn is expressed in physical and mental fatigue, depressive states, frustration, dissatisfaction and sickness.